Application of Quasi Proportional Resonance Control Algorithm in Three-phase Inverter Power - Weiwei GAN; Wei GUO; Ke CHEN; Wentao WANG; Minggao ZENG; Xuebiao PENG (机车电传动)
Nonlinear loads introduce harmonics into the three-phase inverter power system, which damages the electrical equipment. In order to reduce the harmonic content of the inverter output voltage, a harmonic suppression method based on the quasi-proportional resonance control algorithm was proposed. The proposed method mainly suppresses the 5th and 7th harmonics of the inverter output voltage. The traditional instantaneous control method and quasi-proportional resonance method were tested by simulation models and physical experiments. Results show that the quasi-proportional resonance can eliminate specific harmonics in the output voltage, meets the requirements of system dynamic response performance and steady-state accuracy and has a good harmonic suppression effect.